2015
DOI: 10.1164/rccm.201412-2214oc
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Muscle Fiber Weakness and Ubiquitin–Proteasome Activation in Critically Ill Patients

Abstract: Rationale: The clinical significance of diaphragm weakness in critically ill patients is evident: it prolongs ventilator dependency, and increases morbidity and duration of hospital stay. To date, the nature of diaphragm weakness and its underlying pathophysiologic mechanisms are poorly understood.Objectives: We hypothesized that diaphragm muscle fibers of mechanically ventilated critically ill patients display atrophy and contractile weakness, and that the ubiquitin-proteasome pathway is activated in the diap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 172 publications
(210 citation statements)
references
References 63 publications
6
180
0
5
Order By: Relevance
“…Consistent with the view that MuRF1 acts as an atrogin, its expression is intimately associated with muscle wasting in numerous clinical conditions (as reviewed in Bodine and Baehr2) or following exposure to pharmacological treatments (e.g. glucocorticoids, inflammatory cytokines, reactive oxygen species7, 8, 9, 10), while its gene inactivation confers partial resistance to muscle wasting conditions 7, 8, 11, 12. Therefore, several approaches have attempted to down‐regulate MuRF1 activity therapeutically, either directly in vitro via targeted inhibition of MuRF1 by a muscle‐specific small molecule13 and adenoviral knockdowns14, 15 or indirectly in vivo via exercise training16 or antioxidant administration17, which resulted in a significant reduction in muscle wasting.…”
Section: Introductionmentioning
confidence: 55%
“…Consistent with the view that MuRF1 acts as an atrogin, its expression is intimately associated with muscle wasting in numerous clinical conditions (as reviewed in Bodine and Baehr2) or following exposure to pharmacological treatments (e.g. glucocorticoids, inflammatory cytokines, reactive oxygen species7, 8, 9, 10), while its gene inactivation confers partial resistance to muscle wasting conditions 7, 8, 11, 12. Therefore, several approaches have attempted to down‐regulate MuRF1 activity therapeutically, either directly in vitro via targeted inhibition of MuRF1 by a muscle‐specific small molecule13 and adenoviral knockdowns14, 15 or indirectly in vivo via exercise training16 or antioxidant administration17, which resulted in a significant reduction in muscle wasting.…”
Section: Introductionmentioning
confidence: 55%
“…To the best of our knowledge, no studies have been published that document the same effect in non-critically ill humans 37. As an indirect indicator of diaphragm strength, Jaber et al 18 measured tracheal occlusion pressure in response to bilateral phrenic nerve stimulation in intensive care patients undergoing prolonged MV.…”
Section: Discussionmentioning
confidence: 99%
“…The diaphragm seems more sensitive to disuse atrophy than other peripheral skeletal muscles 33 . Several previous studies [33][34][35][36] have shown that critical illness and MV cause atrophy of human diaphragm myofibres. Finally, the abnormalities in muscle function are exacerbated by a decrease in oxygen supply to these muscles, metabolic acidosis, and by certain electrolytic and endocrinological disorders.…”
Section: Other Causes Of Weaning Failurementioning
confidence: 96%